Interferon hyperactivity impairs cardiogenesis in Down syndrome via downregulation of canonical Wnt signaling - Congwu Chi; Walter E. Knight; Andrew S. Riching; Zhen Zhang; Roubina Tatavosian; Yonghua Zhuang; Radu Moldovan; Angela L. Rachubinski; Dexiang Gao; Hongyan Xu; Joaquin M. Espinosa; Kunhua Song (iScience, 2023)
Summary: Congenital heart defects (CHDs) are frequent in children with Down syndrome (DS), caused by trisomy of chromosome 21. However, the underlying mechanisms are poorly understood. Here, using a human-induced pluripotent stem cell (iPSC)-based model and the Dp(16)1Yey/+ (Dp16) mouse model of DS, we identified downregulation of canonical Wnt signaling downstream of increased dosage of interferon (IFN) receptors (IFNRs) genes on chromosome 21 as a causative factor of cardiogenic dysregulation in DS. We differentiated human iPSCs derived from individuals with DS and CHDs, and healthy euploid controls into cardiac cells. We observed that T21 upregulates IFN signaling, downregulates the canonical WNT pathway, and impairs cardiac differentiation. Furthermore, genetic and pharmacological normalization of IFN signaling restored canonical WNT signaling and rescued defects in cardiogenesis in DS in vitro and in vivo. Our findings provide insights into mechanisms underlying abnormal cardiogenesis in DS, ultimately aiding the development of therapeutic strategies.